BIMBINGAN KELOMPOK DALAM MENGATASI STRES - Armila Armila (INSTITUT AGAMA ISLAM NEGERI METRO, 2020)
Group guidance is one of the guidance techniques that seek to help individuals to achieve optimal development in accordance with the abilities of talents, interests, and values ​​that are adopted and implemented in group situations. Group guidance is intended to prevent problems arising in individuals and develop individual potential. The group guidance service has three functions First, the informative function, Second, the development function. Both of these functions for example, group guidance is carried out through the activity of the Home Room, while the third, preventive and creative functions, are used for the treatment of psychological problems such as psychodrama, or sociodrama for the treatment of problems or social conflicts. In this paper the group guidance service is one of the media oriented towards efforts to help individuals develop themselves in order to be more independent, be able to socialize well, be able to practice speaking, responding, giving other people's opinions, being able to work together, caring with others, fostering normative attitudes and behavior as well as other aspects, tolerance and in turn individuals can develop their own potential and can improve their personal communication behavior, and most importantly, learn to take the right decisions for themselves in order to achieve more future goals good.